A tumor-stroma targeted oncolytic adenovirus replicated in human ovary cancer samples and inhibited growth of disseminated solid tumors in mice - Lopez, Maria Veronica (2012)
Targeting the tumor stroma in addition to the malignant cell compartment is of paramount importance to achieve complete tumor regression. In this work, we modified a previously designed tumor stroma-targeted conditionally replicative adenovirus (CRAd) based on the SPARC promoter by introducing a mutated E1A unable to bind pRB and pseudotyped with a chimeric Ad5/3 fiber (Ad F512v1), and assessed its replication/lytic capacity in ovary cancer in vitro and in vivo. AdF512v1 was able to replicate in fresh samples obtained from patients: (i) with primary human ovary cancer; (ii) that underwent neoadjuvant treatment; (iii) with metastatic disease. In addition, we show that four intraperitoneal (i.p.) injections of 5 × 10(10) v.p. eliminated 50% of xenografted human ovary tumors disseminated in nude mice. Moreover, AdF512v1 replication in tumor models was enhanced 15-40-fold when the tumor contained a mix of malignant and SPARC-expressing stromal cells (fibroblasts and endothelial cells). Contrary to the wild-type virus, AdF512v1 was unable to replicate in normal human ovary samples while the wild-type virus can replicate. This study provides evidence on the lytic capacity of this CRAd and highlights the importance of targeting the stromal tissue in addition to the malignant cell compartment to achieve tumor regression.